Protein synthesis in plastids - Zerges, William (Henry Stewart Talks, 2007)
Plastids have complete protein synthesis machinery, Most plastid ribosomal proteins, ribosomal RNAs, translation factors and cisacting translational regulatory elements are homologous to components of bacterial protein synthesis, Plastid-specific components have been identified, Proteins are targeted to thylakoid membranes during their synthesis by plastid ribosomes
Reviewed at 2020/05/01